Geotecnologias no monitoramento de bacias hidrográficas por indicadores ambientais - Souza, Gustavo Ferreira de (Universidade Federal de São Carlos, 2012)
The River Basin Committees (CBHs in portuguese, Comitês de Bacias Hidrográficas) have difficulties in managing water resources because the physiographic units refer to large areas of territorial extension, with numerous problems accumulated over the last decades and distributed throughout the basin. In the State of São Paulo, the Water Resources Management Units (UGRHIs in portuguese, Unidades de Gerenciamento de Recursos Hídricos) are the territorial divisions considered for the management of water resources, under the responsibility of CBHs, with the challenge of mitigating and restoring environmental impacts. In order to fulfill the management functions, support mechanisms are used, such as applying technologies and developing diagnostics to implement water resources policies. This work aims to apply geotechnologies in monitoring and control of water resources, in this sense contribute to the application of technology in the management process of the committee. A database on geographic information systems (GIS) was organized as a support to evaluate the applicability of remote satellite sensors in the identification and calculation of geoenvironmental indicators, according to the development of a geotechnology application roadmap for use and coverage analysis of the project, from the beginning of 1995 to the year 2012. The study was developed in a pilot area in CBH Turvo / Grande (CBH-TG), using the gvSIG platform and the sensors from the Landsat, CBERS, IRS, RapidEye, WorldView-2 and Sentinel-2A satellites. Digital image processing was applied and the results validated through field surveys. The results showed that the satellite image is not limited by its spatial resolution for mapping and monitoring, and that the evolution of the land cover and occupation was conditioned by the transformation of the field of pasture by agriculture in a period of 20 years, with direct impacts in the areas of permanent preservation, legal reserve, siltation and the quantity of water resources. From a spatial analysis of the data crossing in a GIS environment, an environmental vulnerability map was generated that assists in the geoenvironmental interpretation, evidencing with the degree of morphogenesis and pedogenesis. In the analysis of the territorial management of the basin it was evaluated that the delimitations of the basins are imprecise for a management in the scale that a UGRHI needs.
Geotechnologies in basin monitoring hydrographic by environmental indicators
Keywords: Geotecnologias; Geoprocessamento; Sensoriamento remoto; Bacia Hidrográfica; Indicador Ambiental; Gerenciamento; Geotechnologies; Monitoring; Watersheds; Environmental Indicators; Business Management; Remote sensing; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO::CONSERVACAO DE SOLO E AGUA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEODESIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEODESIA::CARTOGRAFIA BASICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEODESIA::FOTOGRAMETRIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOFISICA::SENSORIAMENTO REMOTO; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::CLIMATOLOGIA GEOGRAFICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOCARTOGRAFIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOECOLOGIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOMORFOLOGIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::HIDROGEOGRAFIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::PEDOLOGIA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA REGIONAL::ANALISE REGIONAL; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::CARTOGRAFIA GEOLOGICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::GEOLOGIA AMBIENTAL